Multifunctional conjugated molecules combined with electrospun CuCoP/carbon nanofibers as a modifier of the Pt counter electrode for dye-sensitized solar cells. Issue 34 (1st August 2022) - Lin, Fang-Sian; Sakthivel, Mani; Fan, Miao-Syuan; Wu, Chien-Hsin; Fong, Guan-Lun; Lin, Jiang-Jen; Jeng, Ru-Jong; Ho, Kuo-Chuan
Abstract : A multifunctional modified layer (DPPTPTA@CuCoP/CNF ) was used for the first time in dye-sensitized solar cells, which achieved a conversion efficiency of 25.44 at 6000 lux and ensured long-term stability (90% retention after 3000 h). Abstract : Star-shaped 3, 6-bis(5-(4, 4′-bis(3-azidopropyl)-[1, 1′:3′, 1′-terphenyl]-5′-yl)-thien-2-yl)-2, 5-bis(2-ethylhexyl)pyrrolo[3, 4- c ]pyrrole-1, 4(2 H, 5 H )-dione (DPPTPTA) is combined with electrospun bimetallic copper–cobalt phosphide decorated on carbon nanofibers (CuCoP/CNF) and used as a modified layer (DPPTPTA@CuCoP/CNF ) on the platinum (Pt) coated counter electrode (CE) of dye-sensitized solar cells (DSSCs). DPPTPTA possesses ladder-like energy levels for efficient charge separation while CuCoP/CNF exhibits high electrocatalytic activity and sufficient electrical conductivity. Overall, the DPPTPTA@CuCoP/CNF heterostructure exhibits attractive performance needed for CE of DSSCs. From electrochemical analysis, it is observed that the DPPTPTA@CuCoP/CNF modified layer ensures efficient charge transfer at the CE/electrolyte interface with low charge transfer resistance. Moreover, the CE/electrolyte interface possesses a small electron recombination rate, since the modified layer has good charge separation ability. Under 1 sun (AM 1.5G, 100 mW cm −2 ) conditions, the proposed DSSC achieved a photoelectric conversion efficiency ( η ) of 9.50%, an open-circuit voltage ( V OC ) of 827 mV, a short-circuit current density ( J SC ) of 16.25 mA cm −2, and a fill factor (FF) of 0.71. Under indoor conditions, the η value at 6000 lux (1.89 mW cm −2 ) reached 25.44%. Finally, the porous three-dimensional nanofiber structure of modified layer can ensure the long-term stability (90% retention after 3000 h). Thus, the DPPTPTA@CuCoP/CNF modified layer-based DSSC can be considered as a promising device for possible renewable energy applications.